Effect of nutrition education and counseling training on pediatric residents' knowledge and counseling practices and on caregivers' knowledge and complementary feeding practices - Garcia, Edilberto B.
One of the determinants of malnutrition is the inadequate knowledge of caregivers on appropriate complementary food and good feeding practices. Health providers including pediatric residents lack adequate knowledge to provide effective counselling on infant and young child feeding. There is a need to break down the barriers that prevent health providers from giving nutrition counseling to caregivers. To determine the effect of nutrition education and counselling training on complementary feeding, on the knowledge and counseling practices of resident physicians and on the knowledge and feeding practices of caregivers of 6-24 months old infant seen at the Outpatient department of St Luke?s Medical Center. A non experimental pre test and post-test study design was employed in this study which included 20 pediatric residents and 60 caregiver-infant pairs selected from the outpatient department of the Institute of Paediatrics and Child Health, St. Lukes Medical Center (IPCH-SLMC). An interview schedule was used to obtain nutrition knowledge and self-reported counselling practices pre-test and post-test for both the residents and feeding practices for the caregivers. Counseling skills of the residents were video-taped and evaluated by the investigator and two other consultants. Additionally, the residents attended a six-hour nutrition education and counselling training on complementary feeding. Paired t-test was used to compare pre-test and post-test scores of residents and caregivers before and after the residents? training. Satisfaction rate on the outcome of training of residents was also obtained from the residents and caregivers. Among the residents, statistically significant increases were observed in (a) knowledge scores, 4.7 points (95% Cl 3.28 ? 6.12) (p=0.0000), (b) self-reported practice on complementary feeding, 4.05 points (95%Cl 0.6 ? 7.5) (p=0.0238). Counseling skills as observed by three evaluators improved by 1.85 points (95% Cl 1.06-2.64) (p=0.0001) which was also statistically significant. The caregivers? knowledge scores as measured by the nutrition test increased significantly by 1.15 points (95% Cl 0.76-1.54) (p=0.0000), while the self-reported practice score on complementary feeding decreased by 0.25 points (95% Cl -1.63-1.13) (p=0.71) although this was not statistically significant. Based on the ?satisfaction survey,? residents and caregivers were both satisfied with the outcome of the consultation after the nutrition education and counselling training of the residents. Conclusions: Nutrition education and counselling training on complementary feeding among paediatric residents improved significantly their personal knowledge and counselling practices as well as the knowledge of caregivers. The caregivers? feeding practices remained ?good? with no significant change from baseline to two weeks after the consultation. Recommendations: An experimental design using a control group and randomization method would help control for confounders like other possible sources of information that may have influenced the residents. A longer time for follow-up among caregivers may be employed to document the stages of behaviour change in feeding practices which according to Transtheoretical Model theory on behaviour change may take up to six months. Development of information education communication (IEC) materials on complementary feeding to be given to caregivers during consultation will support and ensure success of adequate promotion of appropriate feeding practices. Nutrition education and counselling training on complementary feeding should be routinely adopted in the curriculum of undergraduate medical students and of paediatric residents to address the lack of knowledge and confidence in giving nutrition counselling.